KEPEMIMPINAN BERBASIS NILAI: MENERAPKAN AJARAN KRISTUS DALAM ORGANISASI - Nining Saputri Simon; Oktavia Marni Dani, Nelchy Boboy, Karmiyati Sabuna (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Christian leadership based on spiritual values and the word of God, and how to apply them in various contexts, both in the church, organizations, and society. Christian leadership emphasizes a close relationship with God, integrity, a clear vision, and responsibility in carrying out tasks. Based on the example of Jesus Christ, Christian leaders are expected to be able to demonstrate love, sacrifice, and good service to others. In addition, this study also shows that secular leadership, although not always religious, contains universal principles that are in line with Biblical values